The role of social exchange theory on internal team performance: a conceptual review of Malaysian Search and Rescue (SAR) team / Norsyazwani Ab Halim and Azlyn Ahmad Zawawi - Ab Halim, Norsyazwani; Ahmad Zawawi, Azlyn (2021)
Team performance in Search and Rescue (SAR) refers to the engagement of effort between SAR teams that could lead them to achieve their shared goals and objectives, saving victims' lives during the SAR mission. According to Morgeson et al. (2005), SAR team performance is all the missions and operations formally carried out by the teams that could impact the teams' goal accomplishment. There are a few critical elements to building team performance in SAR teams (Katzenbach & Smith, 1993). SET is based on the premise that a person will act in accordance with the rewards and punishment that they are most likely to receive (Cook & Rice, 2006). In that context, rewarded habits would possibly cause repetitions and vice versa. Emerson (1976) claimed that action would continue to flow only if it is contingent upon a valued return. SET was also built on the idea that, in performing behaviors, there are elements of reciprocity as an exchange rule (Cropanzano & Mitchell, 2005). In the context of team performance, this means that for any behavior performed by team members, they also hope to earn some sort of rewards in exchange. Social exchange is expected to occur when team members feel that they have received useful team inputs. For instance, team members will be more motivated to achieve performance when they feel that the other members provide quality relationships for an exchange.